Tourist-Host Interactions and Tourism Experiences: A Study of Tourism Experiences and Effects in Sikles, Nepal - Upadhyay, Prakash (The Gaze: Journal of Tourism and Hospitality, 2020)
It is necessary to create a positive interaction between host and tourist for achieving and maintaining sustainable tourism in a destination. The quality and frequency of interaction between tourist and resident contributes to tourists’ experience, perception of the visited destination, local socio-cultural and environmental status, and acceptance and tolerance of tourists by residents. The key objective of this study is to examine the international tourist experiences, interaction with residents, and the social, cultural and environmental effects of tourism in the host community of Sikles. The research was conducted among 50 international tourist visiting Sikles during January, 2019. The results shows that village tourism of Sikles is a phenomenon representing nature conservation, adventure, life style, experience and above all benefit to the local people. Foreign tourist visited Sikles for adventure-trekking, relaxes and rest and their expectations were fulfilled during their visit, and there prevails a jovial relationship between tourist and host with a broad spectrum of tourism experiences and impact on local community. However, tourism as a global phenomenon has brought both positive and negative impacts on economic, environmental and social lives which are crucial for leading changes and revitalization of local society, culture and economy of Sikles. Indigenous Gurung culture has become more differentiated and the forces of tourism are strong enough to influence every spheres of local life. But, the effervescent interaction between tourist and host, experiences, perspicacity of jovial relations, the budding social, cultural and environmental challenges has amplified the awareness of both tourist and host for sustainable eco-friendly tourism.